INCLUSIVE EDUCATION POLICY: SCHOOL MANAGEMENT AND STUDENT SPECIAL NEEDS SERVICES - Rina Wijayanti; Irda Suriani (Adisam Publisher, 2025)
Inclusive education is an approach to the education system that aims to bring students with special nee ds and other students together in the same learning environment. It advocates for modifications in curriculum, teaching methods and school facilities to meet the diverse needs of all students. In essence, inclusive education seeks to create equal learning opportunities for every student, respecting differences and integrating support that enables each individual to reach their potential. The study conducted in this research used the literature research method. The results show that schools that successfully implement inclusive programs tend to have strong governance, support continuous professional development for teachers and involve active collaboration between school, home and community. The findings also confirm that effective implementation of inclusive education not only helps students with special needs but also reinforces the values of inclusiveness within the school community thus fostering a more harmonious and productive learning environment.